The Influence of Social and Parental Economic Conditions on Students' Motivation to Pursue Higher Education - Miranti Paparang; Radia Hafid; Yulianti Toralawe; Melizubaida Mahmud; Ardiansyah Ardiansyah (International Journal of Educational Development, 2025)
The purpose of this study was to determine (1) the influence of social conditions on the motivation to continue education to college for class XII students at SMA Negeri I Lolak (2) the influence of people's economy on the motivation to continue education to college for class XII students at SMA Negeri 1 Lolak (3) the influence of social conditions and parents' economy on the motivation to continue education to college for class XII students at SMA Negeri 1 Lolak. This study uses a quantitative approach, the data used is primary data obtained from distributing questionnaires to class XII students at SMA Negeri I Lolak. The sample in this study was 59 respondents. Data collection techniques used in this study were observation, questionnaires,documentation and research data were analyzed using multiple regression models, hypothesis testing and determination coefficient tests. The results of the study showed that (1). social conditions influence the motivation variableto continue studies to college for class XII students at SMA Negeri 1 Lolak (2) parents'economy influences the motivation variable to continue education to college for class XII students at SMA Negeri 1 Lolak (3). Social conditions and economic variables of parents have a joint effect on the variable of motivation to continue education to college for students of Class XII of SMA Negeri 1 Lolak. The results of this study indicate the coefficient value of the determination of the variables of social and economic conditions of parents to the motivation to continue education to college with a Very Strong influence interpretation. The coefficient of determination (Rsquare) value shows the percentage of the influence of variable XI (Social Conditions of Society) and variable X2 (Parents' Economy on variable Y (Motivation to continue education)which is 62.3.